Produção da cultura do morango semi-hidropônico em diferentes sistemas de cultivo - Castro, Hamilton Abraham Weimar (2017)
Strawberry is a crop of great economic importance in the horticultural sector at national and international level, due to the high demand of labor, generating jobs and consequently improving the quality of life of families. The area of strawberry production grows every year and with this arises the need to develop new production technologies and choices of cultivars appropriate to adapt to the southern region of Mato Grosso. The objective was to evaluate the performance, production and quality of strawberry fruits using three cultivars submitted to different cultivation systems in protected environment. The experiment was conducted at the Federal University of Mato Grosso, Campus of Rondonópolis, under greenhouse conditions. The design was in randomized blocks, in subdivided plots, using three cropping systems as main plot: Zeer pot (ceramic blocks), plastic pots and Slab (plastic bags), and the subplots with three strawberry cultivars: San Andreas, Oso Grande and Albion, with four repetitions, totaling 36 subplots. For the formation of the substrate were mixed soil and commercial substrate. The irrigation system was drip irrigation, using self- compensating drippers (Naan). A nutrient solution was prepared according to the stages of development of the strawberry. Performance characteristics were evaluated as leaf and flower numbers, leaf area, shoot dry mass; the productive part of the plants and the quality of the fruits were also evaluated. The crops systems influenced the performance of strawberry plants in the protected environment in the region of Rondonópolis-MT, except for the fruit qualities that were not influenced by cropping systems. The systems that provided better development of the strawberry cultivars were the plastic pots and Slab, respectively, while the ceramic block system provided the least development of the strawberry plants. The San Andreas and Albion varieties had the greatest plant development.